FRAGMENTASI BUDAYA DIASPORA DIGITAL INDONESIA DI PLATFORM GLOBAL - Ronal Kiding Allo; Muh. Syahrul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This article formulates a phenomenon experienced by the digital diaspora in Indonesia, where cultural fragmentation has affected global social media platforms, including YouTube, TikTok, Instagram, and Twitter. Using qualitative methods through content analysis and netnography, this study explores how their cultural identities are navigated within the Indonesian diaspora community in the transnational digital space. It is proven that the Indonesian digital diaspora experiences three main forms of fragmentation: identity fragmentation (the split in self-representation between local values ​​and global norms), community fragmentation (the development of subgroups based on region, religion, and generation), and narrative fragmentation (the discursive battle between nostalgia, nationalism, and cultural assimilation). Global platforms play a dual role: as spaces for cultural expression and as agencies that reshape cultural practices through algorithms and content policies. This article argues that fragmentation is not solely a negative phenomenon, but rather a reflection of the dynamic negotiation of identity in the context of digital globalization.